Fabrication of a novel bone ash-reinforced gelatin/alginate/hyaluronic acid composite film for controlled drug delivery - ALEMDAR YAYLA, NESLİHAN (ELSEVIER SCI LTD, 2016)
In this study, a novel pH-sensitive composite film with enhanced thermal and mechanical properties was prepared by the incorporation of bone ash at varying concentrations from 0 to 10 v.% into gelatin/sodium alginate/hyaluronic acid (Gel/SA/HyA) polymeric structure for colon-specific drug delivery system. Films were characterized by FT-IR, SEM, and XRD analyses. Thermal and mechanical performances of films were determined by DSC, TGA and universal mechanical tester, respectively. Results proved that thermal stability and mechanical properties of bone ash-reinforced composite films improved significantly with respect to that of neat Gel/SA/HyA film. Cytotoxicity assay for composite films was carried out by using L929 cells. Water uptake capacity of films was determined by swelling test. Herein, release experiments of 5-Fluorouracil (5-FU) were performed in two different solutions (pH 2.1 and 7.4). The results assured that Gel/SA/HyA film containing BA could be considered as a potential biomaterial for controlled drug delivery systems. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Polymeric network; Bone ash; Mechanical properties; pH-sensitive release; Drug delivery systems; GELATIN; HYDROGEL; BIOCOMPATIBILITY; CHITOSAN